ADAPTIVE CLOTHING FOR FEMALES WITH ARTHRITIS IMPAIRMENT - Naheed Azher; Muhammad Saeed (Journal of University Medical & Dental College, 1970)
ABSTRACT Clothing is one of the basic needs of human life. It plays an important role in the development of an individual, which is equally true in case of physically challenged. Adaptive clothing can offer arthritis women an easy, time saving and pain free way to dress. Keeping in view the importance of clothing in human life, three sets of garments were specially designed for females with Rheumatoid arthritis impairment. Independence and self-confidence of these specially designed garments were assessed by wear trail test. Research process comprised of assessing clothing needs and problems faced while donning and doffing and providing independence and self-confidence through co-designing and evaluating the effectiveness of that adaptive garment after wear trail of three weeks. A qualitative method was used, employing data collection by in-depth interviews and observations. The researcher did a detailed thematic analysis using predetermined codes to aid analysis, of all the information gathered from three female participants of the study. The researcher found what was missing in the clothing that the participants wore in their regular lives, and worked with them to find out what they wanted in the adaptive clothing that provides them independence and self-confidence .The special features incorporated in the newly designed functional garments were found to be most comfortable and practicable. All the three participants expressed that the specially designed garments were not only attractive but also functional and can be used as casual wear or outer wear. The adaptive clothing was a successful mean to satisfy the participant’s needs and preferences in a better way.